Individual predictors of sensorimotor adaptability - Seidler, Rachael D.; Mulavara, Ajitkumar P.; Bloomberg, Jacob J.; Peters, Brian T. (Frontiers in Systems Neuroscience, 2015)
There are large individual variations in strategies and rates of sensorimotor adaptation to spaceflight. This is seen in both the magnitude of performance disruptions when crewmembers are first exposed to microgravity, and in the rate of re-adaptation when they return to Earth’s gravitational environment. Understanding the sources of this variation can lead to a better understanding of the processes underlying adaptation, as well as provide insight into potential routes for facilitating performance of “slow adapters”. Here we review the literature on brain, behavioral, and genetic predictors of motor learning, recovery of motor function following neural insult, and sensorimotor adaptation. For example, recent studies have identified specific genetic polymorphisms that are associated with faster adaptation on manual joystick tasks and faster recovery of function following a stroke. Moreover, the extent of recruitment of specific brain regions during learning and adaptation has been shown to be predictive of the magnitude of subsequent learning. We close with suggestions for forward work aimed at identifying predictors of spaceflight adaptation success. Identification of “slow adapters” prior to spaceflight exposure would allow for more targeted preflight training and / or provision of booster training and adaptation adjuncts during spaceflight.